Coronavirus disease (COVID‐19): An updated review based on current knowledge and existing literature for dermatologists. Issue 4 (26th June 2020) - Kaur, Ishmeet; Sharma, Aseem; Jakhar, Deepak; Das, Anupam; Aradhya, Sujala Sacchidanand; Sharma, Rashmi; Jindal, Veenu; Mhatre, Madhulika
Abstract: The world entered the year 2020 with reports of the emergence of a new viral illness in Wuhan city, Hubei province, China. In January 2020, severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) was identified to be the causative novel coronavirus for the cluster of patients suffering from pneumonia in China. The disease was later named as coronavirus disease (COVID‐19) and was declared a pandemic by the World Health Organization on March 11, 2020. Several studies, since then, have tried to study and explain the origin of SARS‐CoV‐2, its structure and pathogenicity, epidemiology, modes of transmission, spectrum of illness and causes of mortality and morbidity. The current management strategies focus on supportive care and prevention of complications. With no definite treatment, as of now, encouraging reports of some anti‐viral and anti‐malarial drugs in the management of COVID‐19 generate some hope. This review intends to cover the current known aspects of COVID‐19 and SARS‐CoV‐19, based on the available literature.